Managers at work - Blake, Gary (Research management (Now: research technology management))
Gary Blake explains how Quality in R&D Demands Right Writing. Followed by Jay Campbell, Russ Gillis, Cliff Sacks and Joseph Timko on Communicating Project Status to Management-Simply.